Frequency and Location of Supernumerary Teeth in a Private Hospital of Karachi City - Syed Ahmed Omer; Seema Nisar; Perveen Memon; Hamidullah Arif; Raza Ali; Samra Faheem (Journal of Bahria University Medical and Dental College)
Study Design and Setting: Cross-sectional Study was conducted at Mamji Hospital, Karachi from June 2017 to June 2019. Methodology: A total of 2160 patients seen and out of which 45 clinically diagnosed patients of supernumerary teeth were participated in this study. Supernumerary teeth were classified on the basis of location. Descriptive statistics were checked by means of percentages and frequency of all variables. Chi-Square test was applied, P-value < 0.05was considered significant. Results: The total patients were 45 which comprised of 26 male and 19 females with ages ranging from 15 to 60 years. The prevalence of ST was 1.59%, the higher predilection of supernumerary teeth was seen in males than females. The male to female’s ratio was 1.36:1. On the basis of location ST were further classified on Mesiodens, Paramolars and Distomolars category. Of the 45 supernumerary teeth, 36 were had Mesiodens (m= 62.1%, f=37.8%), 5 were Paramolars (m=60%, f=40%) and 3 were Distomolars (m=0, f= 100%). Conclusion: The present study findings showed high prevalence of ST was dominant in males. Present study emphasizes the timely diagnosis and appropriate management of supernumerary teeth to avoid unwanted complications